Essential oil and glycosidically bound volatiles of Thymus pulegioides L. growing wild in Croatia - Radonić, Ani (Array, 2008)
Abstract: The present paper represents the continuation of our research of free (essential oil) and glycosidically bound volatile compounds from Croatian wild-growing aromatic plants. The essential oil and glycosidically bound volatile compounds were isolated from the fresh and dried plant material of Thymus pulegioides L. at three stages of plant development and analysed by gas chromatography-mass spectrometry (GC-MS). The most abundant constituents in essential oils were geraniol and linalool followed by thymol, g-terpinene, thymol methyl ether, borneol and geranyl acetate, all of which showed quantitative variations during the plant development stages and whether fresh or dried plants were used for essential oil isolation. After enzymatic hydrolysis of glycosidic fractions, the GC-MS analysis of volatile aglycones revealed eugenol, geraniol and 1-octen-3-ol as the main aglycones in all samples. Other important aglycones were thymoquinone, 2-phenylethanol, 3-hexenol, 3-octanol, benzyl alcohol and linalool. Quantitative variations were observed when the aglycones were analysed at three different stages of plant development. Because of the high geraniol content in the essential oils and in the aglycone fractions this Thymus pulegioides L. could be interesting as a fragrant material for perfume industry or for food flavouring